Engineering 2D Mesoporous Silica@MXene‐Integrated 3D‐Printing Scaffolds for Combinatory Osteosarcoma Therapy and NO‐Augmented Bone Regeneration. Issue 14 (28th February 2020) - Yang, Qianhao; Yin, Haohao; Xu, Tianming; Zhu, Daoyu; Yin, Junhui; Chen, Yixuan; Yu, Xiaowei; Gao, Junjie; Zhang, Changqing; Chen, Yu; Gao, Youshui
Abstract: The rising concerns of the recurrence and bone deficiency in surgical treatment of malignant bone tumors have raised an urgent need of the advance of multifunctional therapeutic platforms for efficient tumor therapy and bone regeneration. Herein, the construction of a multifunctional biomaterial system is reported by the integration of 2D Nb2 C MXene wrapped with S‐nitrosothiol (RSNO)‐grafted mesoporous silica with 3D‐printing bioactive glass (BG) scaffolds (MBS). The near infrared (NIR)‐triggered photonic hyperthermia of MXene in the NIR‐II biowindow and precisely controlled nitric oxide (NO) release are coordinated for multitarget ablation of bone tumors to enhance localized osteosarcoma treatment. The in situ formed phosphorus and calcium components degraded from BG scaffold promote bone‐regeneration bioactivity, augmented by sufficient blood supply triggered by on‐demand NO release. The tunable NO generation plays a crucial role in sequential adjuvant tumor ablation, combinatory promotion of coupled vascularization, and bone regeneration. This study demonstrates a combinatory osteosarcoma ablation and a full osseous regeneration as enabled by the implantation of MBS. The design of multifunctional scaffolds with the specific features of controllable NO release, highly efficient photothermal conversion, and stimulatory bone regeneration provides an intriguing biomaterial platform for the diversified treatment of bone tumors. Abstract : The multifunctional biomaterial system integrates photonic hyperthermia of MXene in near infrared (NIR)‐II biowindow with precisely controlled nitric oxide (NO) release for multitarget ablation of bone tumors and localized osteosarcoma treatment. The in situ formed phosphorus and calcium components degraded from bioactive glass (BG) scaffold promote bone‐regeneration bioactivity, which is further augmented by sufficient blood supply triggered by on‐demand NO release.